Pacing in children - Harinder R Singh; Anjan S Batra; Seshadri Balaji (Wolters Kluwer Medknow Publications, 2013)
The implantation of cardiac pacing devices in children and young adults can be challenging and different from the adult population due to their smaller size, their longer life expectancy, and anatomical variations associated with congenital heart defects. A knowledge of indications, pacing leads and devices, anatomical variations, and the technical skills are important for those who implant and care for children with pacemakers. In this review we attempt to discuss these specific points of cardiac pacing in children and young adults.